Dengue virus serotypes and related factors in children with dengue hemorrhagic fever in Southern Vietnam - Quang Tran, Khai; Hung Pham, Van; Thi Ngoc Tran, Trieu; Thao Mai, Chi; Kieu Anh Pham, Tho; Hoang Ngo, Toan; Bui Thai Nguyen, Huy; Manh Nguyen, Cuong; Van Duong, Hieu; Minh Nguyen, Phuong (The Journal of Infection in Developing Countries, 2024)
Introduction: After the Coronavirus Disease 2019 pandemic, a high number of cases and severe dengue in children were reported in some provinces in the south of Vietnam. This study aimed to determine the distribution of dengue virus serotypes and their correlation with demographic factors, disease severity, clinical manifestations, and laboratory findings. Methodology: This study employed a cross-sectional design. Ninety-six dengue-infected children admitted to Can Tho Children's Hospital between October 2022 and March 2023 were included. Confirmation of dengue infection was achieved through the real-time polymerase chain reaction (RT-PCR). Results: Among the identified serotypes, DENV-2 accounted for the highest proportion (71.87%), followed by DENV-1 (23.96%), and DENV-4 (4.17%). DENV-3 was not detected. No significant demographic, disease severity, or laboratory differences were observed among the identified dengue serotypes. However, DENV-2 was associated with a higher occurrence of mucous membrane hemorrhages and gastrointestinal bleeding compared to other serotypes. Conclusions: Although DENV-2 was the most prevalent serotype responsible for dengue in children in southern Vietnam, it did not lead to more severe cases compared to other serotypes. This finding is crucial for evaluating the illness’s prognosis.